Essays in Development Economics. The impact of investment promotion on attracting foreign direct investment in developing countries - LE, VAN THI HAI (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Economics, 2018)
The importance of foreign direct investment (FDI) in economic development is increasingly acknowledged. FDI not only brings additional capital to the host economy, but foreign-invested enterprises also play a part in the transfer of technology, creating jobs and generating positive spillovers to domestic firms. Thus, attracting more FDI in order to boost economic development has become a crucial policy of governments throughout the world, especially in developing countries. This thesis consists of three papers that explore the role of investment promotion in developing countries, with a focus on within-country regional investor targeting and source-country investor targeting. My research uses the case of Vietnam, a developing country undergoing the transformation process from a closed economy to a market-oriented economy, to analyse the promotion policies in developing countries. The first paper examines the effectiveness of investment promotion policies aimed at attracting foreign direct investment (FDI) into particular regions within a country. Using the case of Vietnam, we examine whether the spatial targeting policies of the Investment Promotion Agency over the 1998-2013 period impacted on the level of FDI inflows across districts. We also consider different types of targeting policies, and in particular distinguish between policies aimed at encouraging disadvantaged areas and those motivated by efficiency arguments, such as through the establishment of special economic zones. Using data on all registered FDI projects in Vietnam between 1998 and 2013 we find strong evidence to suggest that spatial targeting has a positive impact on registered FDI inflows. There is also evidence that these policies led to higher levels of FDI in the long term, but only in the pre-2006 period. We also find evidence that targeting is particularly effective in relation to industrial parks where we find higher levels of FDI as a result of targeting and that this investment grows over time. The second paper examines the role of targeted promotion techniques in attracting foreign direct investment in the context of a developing country. We construct a panel dataset of all inward FDI projects into Vietnam for the period 1996 to 2016 to explore the impact of investment promotion techniques implemented by the investment promotion agency under the national investment promotion programme. We find evidence that focussed promotion efforts bring more investment from selected countries. Aftercare services in particular, such as help desks, could be a cost-effective method in attracting FDI into developing countries. Our findings also suggest that the intensity of promotion activities in a targeted country contributes to the increase in FDI inflows. The third paper examines the impact of restrictions on inward FDI in the services sector from the perspective of a developing country. Using the case of Vietnam and the restrictions imposed in the services sector under the bilateral trade agreement with the US, we examine the impact of overall barriers and sub barriers on inward FDI. We construct a unique panel dataset of FDI inflows in services in Vietnam to explore the impact of FDI restrictions imposed through these agreements. There is strong evidence that barriers under the bilateral framework not only negatively impact investors from the US, they also negatively impact on inflows from investors in other countries.
APPROVED
Keywords: foreign direct investment; FDI; developing country; promotion; Vietnam; targeting; spatial policies; promotion tools; bilateral investment agreement; promotion policies